Metabolic changes favor the activity and heterogeneity of reactive astrocytes. (June 2022) - Xiong, Xiao-Yi; Tang, Yong; Yang, Qing-Wu
Abstract : Reactive astrocytes undergo morphological, molecular, metabolic, and functional remodeling in response to central nervous system (CNS) damage. However, we still know very little about how the metabolic switching of astrocytes influences, or is influenced by, reactive astrocytes in response to neurological diseases. In this review, we initially cover a brief introduction into reactive astrocyte function under pathological conditions. Subsequently, we summarize the emerging roles of glucose and lipid metabolism in reactive astrocytes in the context of CNS injury to provide a new insight into metabolic mechanisms of reactive astrocyte-mediated neuroprotection or damage. Finally, we propose that deciphering the mechanistic link between astrocyte heterogeneity metabolism and improved methods is an emerging frontier for the therapeutic investigation of CNS injury and disease. Highlights: The morphological and functional diversity of astrocytes, named astrocyte heterogeneity, depends largely on their location, microenvironment, developmental stage, and stimuli. Increasing evidence suggests that simple binary divisions of reactive astrocytes into good versus bad or neurotoxic versus neuroprotective cannot represent the heterogeneity of reactive astrocytes. Knowledge of metabolic alteration (e.g., glucose and lipid metabolism) in influencing the phenotype of reactive astrocytes in neurological diseases provides novel insights into the potential causal relationships between metabolic changes and astrocyte heterogeneity. A deep deciphering of the initiating metabolic mechanisms that determine the heterogeneity of reactive astrocytes may provide therapeutic targets for related neurological disorders.